2006
DOI: 10.1158/1078-0432.ccr-06-0992
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Tropism-Modified Measles Virus in Folate Receptor–Targeted Virotherapy of Ovarian Cancer

Abstract: Purpose: Attenuated measles viruses are promising experimental anticancer agents currently being evaluated in a phase I dose escalation trial for ovarian cancer patients. Virus attachment, entry, and subsequent intercellular fusion between infected and uninfected neighboring cells are mediated via the two measles receptors (CD46 and SLAM). To minimize potential toxicity due to measles virus–associated immunosuppression and infection of nontarget tissues, we sought to develop an ovarian cancer exclusive fully r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 48 publications
0
66
0
Order By: Relevance
“…These strategies include use of anti-FRα antibodies [10] or folic acid-conjugates to localize drugs [28][29][30], imaging compounds [31][32][33], T cells [34,35], nanoparticles [36], or oncolytic viruses [37] to FRα-expressing tumors. Besides these efforts, we have recently shown that FRα may have potential as a target for immunotherapeutic approaches in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These strategies include use of anti-FRα antibodies [10] or folic acid-conjugates to localize drugs [28][29][30], imaging compounds [31][32][33], T cells [34,35], nanoparticles [36], or oncolytic viruses [37] to FRα-expressing tumors. Besides these efforts, we have recently shown that FRα may have potential as a target for immunotherapeutic approaches in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CD133 cDNA fragment was sub-cloned into a lentiviral-based vector (pHR-SIN-CSGW) (Hasegawa et al, 2006).…”
Section: Cloning Of Human Cd133 Cdnamentioning
confidence: 99%
“…[8][9][10][11][12] MV-NIS is an Edmonston-lineage MV that expresses the human sodium iodide symporter (hNIS) (Figure 2). 12 The NIS protein is normally expressed in the thyroid, mammary glands, stomach, and salivary tissue.…”
mentioning
confidence: 99%